Comparative longevity and low-temperature storage of seeds of Hydatellaceae and temporary pool species of south-west Australia - Tuckett, R.; Merritt, D.; Hay, F.; Hopper, S.; Dixon, Kingsley (2010)
The comparative longevity of seeds of species from the early-angiosperm group, Hydatellaceae, along with other temporary wetland aquatics from the South-west Australian Floristic Region were tested under standard experimental storage conditions. In contrast to recent hypotheses proposing that seeds from basal angiosperm species may be short-lived in storage, seeds of the Hydatellaceae species (Trithuria submersa Hook.f. and T. austinensis D.D.Sokoloff, Remizowa, T.Macfarlane and Rudall) were longer-lived than the other temporary wetland aquatic species tested. Seeds of Glossostigma drummondii Benth. (Scrophulariaceae), Myriophyllum petreaum Orchard and M. balladoniense Orchard (Haloragaceae), lost viability quickly and are thus predicted to be short-lived in seed bank storage. To assist seed bank conservation programs, the effect of seed moisture content on the viability of seeds stored for 1, 6 and 12 months at -18°C or in vapour phase cryopreservation (-150°C) was determined. Seeds of all species survived storage at both temperatures for up to 12 months, provided seed equilibrium relative humidity was below ~50%. Given the high conservation value of Hydatellaceae species and the potential short-lived nature of seeds of some of the species, we recommend that ex situ conservation programs for these aquatic species should consider cryopreservation as a means to maximise the longevity of their seeds. © CSIRO 2010.